Temporäre Gärten. - (:unkn) unknown (My University, 2003)
Dokumentation von 117 Projekten aus den Jahren 1997 bis 2003. difu
Keywords: Landschaft; Garten; Standort; Pflanze; Stadtlandschaft; Landschaftsgestaltung; Temporärer Garten; Landschaftsarchitektur